3x-3(7x+11)=-153

Simple and best practice solution for 3x-3(7x+11)=-153 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-3(7x+11)=-153 equation:


Simplifying
3x + -3(7x + 11) = -153

Reorder the terms:
3x + -3(11 + 7x) = -153
3x + (11 * -3 + 7x * -3) = -153
3x + (-33 + -21x) = -153

Reorder the terms:
-33 + 3x + -21x = -153

Combine like terms: 3x + -21x = -18x
-33 + -18x = -153

Solving
-33 + -18x = -153

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '33' to each side of the equation.
-33 + 33 + -18x = -153 + 33

Combine like terms: -33 + 33 = 0
0 + -18x = -153 + 33
-18x = -153 + 33

Combine like terms: -153 + 33 = -120
-18x = -120

Divide each side by '-18'.
x = 6.666666667

Simplifying
x = 6.666666667

See similar equations:

| w/8-2=1 | | 66-2x=82-3x | | 9f-(-28)=91 | | 6x+x=2(1+3x)-2(1-x) | | 10g-g=9 | | 8=20-2n | | 4(9+3x)-12=6 | | 4x+1x+4=8x-3x+4 | | X+6+7-5=18+4 | | -14=h+7 | | 5(t-87)=10 | | -5(c-89)=-30 | | 13.7b-3=3.43b | | 74-2x=89-3x | | 13.7b-3=3-43b | | 48=12xn | | 19=5a-6 | | -189=-2x-3(7x+17) | | 81-x=94-2x | | 99.60=9.1a+72.3 | | 36=9(r-2) | | 70-3x=130-43x | | 35+42=12+x | | 9x+9=8x+4 | | 5x+7(7+3x)=4(9-8)+7 | | X+19=7+20 | | 99=98s+1 | | 8a^2+10ab^2+4ab+5b^3=0 | | 81-2x=92-3x | | 28=2w+24 | | f(0)=2x^3-5 | | 1.5sin(x)=sin(3x) |

Equations solver categories